Vestibular rehabilitation: Correlation of the sensory organization test and the Dizziness Handicap Inventory - Sousa, Sofia (2018)
Objective: Evaluation of the effects of Vestibular Rehabilitation (VR) in patients with peripheral vestibular hypofunction in postural stability (through the sensory organization test-SOT) on the SYNAPSYS platform) and in perceived disability (through the Dizziness Handicap Inventory-DHI questionnaire). Study Design: A prospective observational study. Material and methods: Evaluation of patients with uncompensated peripheral vestibular hypofunction who underwent VR from January 2015 to December 2017 at the Department of Otorhinolaryngology at CHTV. The clinical history, otoneurological examination, and DHI and SOT before and after VR were evaluated. Results: 24 patients were evaluated, 80% had unilateral peripheral vestibular hypofunction and 20% bilateral. The symptoms presented included dizziness, imbalance, instability, oscillopsia and fall. After VR, there was an improvement of 51.85% in total DHI, 31.24% in the antero-posterior plane SOT, and 21.05% in the medial-lateral plane. Conclusion: RV with the aid of posturography platforms allowed a significant improvement in postural stability and perceived disability in patients with both uni and bilateral noncompensated bilateral deficits.